(untitled) (Journal of Health Sciences, 2016)
Introduction: Personal hygiene is one of the most important determinants of health. A scale of personal hygiene is a useful tool to evaluate effects of health care interventions. The aim of this study was to develop a new, reliable, and valid measurement scale which can be used to evaluate the hygiene status of children, as well as the effects of the interventions.Methods: A total of 248 students and their parents, from Hatay Province in Turkey, participated in this school-based, cross-sectional study. An item pool was created for the Antioch Child Hygiene Scale (ACHS). Same questions were asked both for children (ACHS-C) and parents (ACHS-P) Data were collected in September 2013. Face validity, Cronbach's alpha, split-half, test-retest, factor analysis, and parallel form reliability were determined for the ACHS.Results: Twelve items that showed a weak correlation were removed from the ACHS. The mean score (standard deviation) was 159.4 ± 9.2 for ACHS-C and 152.2 ± 16.9 for ACHS-P. Cronbach's alpha for ACHS-C was 0.82 in the first test and 0.87 in the retest. Cronbach's alpha for ACHS-P was 0.91 in the first test and 0.94 in the retest. Split-half correlation was 0.59 for ACHS-C and 0.75 for ACHS-P. Correlation between pre-test and post-test scores was 0.54 for ACHS-C and 0.64 for ACHS-P (p < 0.001). In the principle component analysis, (Eigen value was taken greater than 1), 20 components for ACHS-C and 13 components for ACHS-P were extracted. Conclusions: Although both ACHS forms (i.e., ACHS-C and ACHS-P) were reliable in assessing the hygiene status of children, the reliability was higher for ACHS-P. In addition, validity should be improved in both forms of the ACHS. Nevertheless, both scales can be used to assess the hygiene status in school children.